Safety and efficacy of a multi-ingredient thermogenic pre-workout supplement during low-intensity running in females - Erickson, Jamie R. (My University, 2017)
The purpose of this study was to examine the acute effects of a thermogenic pre-workout supplement on oxygen uptake (V02), pulmonary ventilation (\TE), carbon dioxide output (VC02), respiratory exchange rate (RER), energy expenditure (EE), heart rate (HR), systolic blood pressure (SBP), and diastolic blood pressure (DBP). Twelve female subjects (mean± SD: age, 25.3 ± 9.4 years; weight, 61.2 ± 6.8 kg) defined as aerobicallytrained volunteered for this randomized, double-blinded, placebo-controlled, crossover study. Subjects performed an incremental running test to exhaustion on the treadmill to determine ventilatory threshold. On three separate laboratory visits, each subject consumed a standardized meal following overnight fasting and were randomly assigned to ingest the supplement (1 or 2 servings) or placebo and ran at a constant velocity at 90% VT for 30 minutes on the treadmill. The findings of the separate one-way ANOVAs with repeated measures indicated that there were significant (P<0.05) mean differences in DBP between the I-dose (61±7 to 72 ± 6 mmHg) and 2-dose (66 ± 5 to 75 ± 5 mmHg) conditions, resting SBP (collapsed across time) (I 07 ± 11 mmHg) compared to the 1-dose (102 ± 11 mmHg) and placebo (I 04 ± 12 mmHg) conditions.
Keywords: Kinesiology; Dietary supplements; Running; Exercise tests